Comprehensive review of strategies for lactic acid bacteria production and metabolite enhancement in probiotic cultures: multifunctional applications in functional foods - Loo, Jiun Shen; Siti Nur Hazwani Oslan; Nur Anis Safiah Mokhsin; Rafidah Othman; Zarina Amin; Wipawee Dejtisakdi; Asep Awaludin Prihanto; Tan, Joo Shun (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Lactic acid bacteria (LAB) play a crucial role in probiotics, functional foods, and sustainable biotechnologies due to their ability to produce bioactive metabolites such as short-chain fatty acids, bacteriocins, vitamins, and exopolysaccharides. These metabolites aid in gut health, pathogen inhibition, and enhanced productivity in the food, pharmaceutical, and aquaculture industries. However, the high production cost remains a major challenge, necessitating cost-effective media formulations and bioprocess optimization. This review explores strategies for maximizing LAB yields and functionality through the precision control of key cultivation parameters, including temperature, pH, and agitation speed, ensuring probiotic viability in compliance with regulatory standards (≥106 CFU/g or mL). Furthermore, advances in metabolic engineering, synthetic biology, and the utilization of agro-industrial by-products are driving cost-efficient and eco-friendly LAB production. By integrating scalable fermentation technologies with sustainable resource management, LAB have the potential to bridge the gap between food security, environmental sustainability, and biotechnological innovation. This review provides a comprehensive overview of recent advances in LAB cultivation and bioprocess optimization, ensuring high-quality probiotic production for diverse industrial applications.